Selective oxidation of propane to acrylic acid: effect on Mn loadings onto mixed metal oxide catalyst - Mohd Salim, Rosliza (2011)

(untitled)
Manganese promoted catalysts has been prepared at a fixed composition of Mo1V0.3Te0.23Nb0.125Mn≤nOx (n =0.0005, 0.005, 0.05 at %) by slurry method and has been tested in the selective oxidation of propane to acrylic acid. The modified catalyst shows higher acrylic acid yield 45%, 49% and 47% with respect to the different loading compared to bulk catalyst with 35% acrylic acid yield. The systems have been investigated by XRD, SEM, IR, TG and DSC to further understand the relationship between the physical-chemical properties of the catalysts to their corresponding catalytic performance. The present of mixture of M1 and M2 phase had been proved by XRD which crucial for oxidation of propane to acrylic acid. The FTIR proved the removal of ligands from the dried precursor. The SEM analysis has revealed the multi-phase nature and morphology of the MoVTeNb catalyst. It has further confirmed that the phase formation occurs kinetically after the gas evolution resulting from ligand removal. The thermal analysis data clearly reveal the complex interplay of ligand removal, polycondensation and phase formation occurring in several intertwined processes separated by temperature.